Neo-Cold War in Asia-Pacific and its impact on the Korean peninsula - CASTELLTORT CLARAMUNT, Magi (Journal of the Spanish Institute for Strategic Studies, 2023)
The Chinese military and economic rise has evoked a Sino-American Neo Cold War scenario that has refounded alliances between non-rival Western economies on an Anglo-Saxon core (the US, the UK, Australia) complemented by Japan, India and Canada. The apparent exclusion of South Korea and the strengthening of the Washington-Tokyo axis would recreate a neocolonial model that, combined with the North Korean nuclearization, could destabilize the peninsula, the theater of the first Cold War. Nevertheless, the democratic-capitalist triangle (the US, South Korea and Japan) seems solidly integrated both militarily and economically. The autocratic triangle (China, North Korea and Russia), on the other hand, seems more united by common anti-hegemonic interests than by economic ties, with Russia and North Korea on the rise.